Molecular recognition at interfaces. Adhesion, wetting and bond scrambling - Ciferri, Alberto (Frontiers in Chemistry, 2022)
The quantitative description of the supramolecular interaction occurring at the adhesion surfaces of different polymers has entitled elaborate dissections of contributions to cohesive and surface energies. An alternative analysis is proposed here based on solubility parameters and binding constants that traditionally describe the weakest and relatively larger association energies in polymer blends. The article emphasizes a feature of supramolecular polymers that has not received adequate consideration: the dynamic bond scrambling that allows a most efficient molecular recognition over significant areas of synthetic and biological surfaces.